2012
DOI: 10.1063/1.3678439
|View full text |Cite
|
Sign up to set email alerts
|

Integration of thin film giant magnetoimpedance sensor and surface acoustic wave transponder

Abstract: Passive and remote sensing technology has many potential applications in implantable devices, automation, or structural monitoring. In this paper, a tri-layer thin film giant magnetoimpedance (GMI) sensor with the maximum sensitivity of 16%/Oe and GMI ratio of 44% was combined with a two-port surface acoustic wave (SAW) transponder on a common substrate using standard microfabrication technology resulting in a fully integrated sensor for passive and remote operation. The implementation of the two devices has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Experimental and theoretical results confirmed that the origin of the GMI is classical skin effect [4][5][6]. Although the studies on GMI effect was initially focused in homogeneous materials [1][2][3], great attention has been paid to the heterogeneous materials such as composite wires and sandwiched films [7,8], since it has great advantages over the homogeneous materials such as [9]: (1) the GMI effect was enhanced obviously, which results from the enhanced skin effect of the coating layer caused by electromagnetic interactions between the conductive and ferromagnetic layers; (2) the MI effect can be observed at much lower frequencies; and (3) realization of miniaturization and practicability for sensors.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Experimental and theoretical results confirmed that the origin of the GMI is classical skin effect [4][5][6]. Although the studies on GMI effect was initially focused in homogeneous materials [1][2][3], great attention has been paid to the heterogeneous materials such as composite wires and sandwiched films [7,8], since it has great advantages over the homogeneous materials such as [9]: (1) the GMI effect was enhanced obviously, which results from the enhanced skin effect of the coating layer caused by electromagnetic interactions between the conductive and ferromagnetic layers; (2) the MI effect can be observed at much lower frequencies; and (3) realization of miniaturization and practicability for sensors.…”
Section: Introductionsupporting
confidence: 64%
“…Recently, giant magneto-impendence (GMI) effect has been intensively studied for its potential applications in highly sensitive magnetic sensors with high spatial/temporal resolution since it was firstly observed in Co-based amorphous wires in 1992 [1,2]. Experimental and theoretical results confirmed that the origin of the GMI is classical skin effect [4][5][6].…”
Section: Introductionsupporting
confidence: 51%
“…1). A multi-layer giant magneto-impedance (GMI) sensor, which offers a good compromise between sensitivity and fabrication complexity [10][11][12][13], is utilized to measure the change of the magnetic field. At small bias fields and at high operating frequencies, the impedance of GMI sensors is sensitive to external magnetic fields, due to the strong dependence of the skin effect on the magnetic permeability.…”
Section: A Sensor Conceptmentioning
confidence: 99%
“…The sensor has a rectangular geometry of 100 μm× 4000 μm. The conducting layer is connected to the IDT3 [18].…”
Section: Integrated Saw-gmi Sensormentioning
confidence: 99%
“…This makes it a suitable load for a SAW transponder, which converts this impedance change into a magnitude and phase change of the reflected acoustic waves. In order to reduce the size and improve the level of integration of the senor, a new design of an integrated SAW transponder and thin film GMI sensor has been proposed and developed recently by the authors [17,18]. The SAW transponder and GMI thin film were integrated on the same chip using standard micro-fabrication technology suitable for mass fabrication.…”
Section: Introductionmentioning
confidence: 99%